2021
DOI: 10.1107/s2053230x21006658
|View full text |Cite
|
Sign up to set email alerts
|

The identification and structural analysis of potential 14-3-3 interaction sites on the bone regulator protein Schnurri-3

Abstract: 14-3-3 proteins regulate many intracellular processes and their ability to bind in subtly different fashions to their numerous partner proteins provides attractive drug-targeting points for a range of diseases. Schnurri-3 is a suppressor of mouse bone formation and a candidate target for novel osteoporosis therapeutics, and thus it is of interest to determine whether it interacts with 14-3-3. In this work, potential 14-3-3 interaction sites on mammalian Schnurri-3 were identified by an in silico analysis of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Moreover, the serum 14-3-3η protein levels among patients with normal bone mass (2.73/3.79), osteopenia (3.15/4.86), and osteoporosis (6.34/6.42) were different (χ 2 = 7.974, P < 0.05); and, therefore, the serum 14-3-3η protein level was associated with the bone mass. However, to the best of our knowledge, only one study has explored the possible mechanisms of the role of the14-3-3 protein family in osteoporosis: In silico analysis of the protein sequence of mammalian schnurri-3, a suppressor of mouse bone formation and candidate target for novel osteoporosis therapeutics 3 , identi ed potential 14-3-3σ interaction sites. The study found that 14-3-3η expression was lower at the transcriptional and proteomic levels in osteoporosis than in control samples.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the serum 14-3-3η protein levels among patients with normal bone mass (2.73/3.79), osteopenia (3.15/4.86), and osteoporosis (6.34/6.42) were different (χ 2 = 7.974, P < 0.05); and, therefore, the serum 14-3-3η protein level was associated with the bone mass. However, to the best of our knowledge, only one study has explored the possible mechanisms of the role of the14-3-3 protein family in osteoporosis: In silico analysis of the protein sequence of mammalian schnurri-3, a suppressor of mouse bone formation and candidate target for novel osteoporosis therapeutics 3 , identi ed potential 14-3-3σ interaction sites. The study found that 14-3-3η expression was lower at the transcriptional and proteomic levels in osteoporosis than in control samples.…”
Section: Discussionmentioning
confidence: 99%